A Study On Octane Requirement For Motor Vehicles In Indonesia - F. Batti W Kaslan (Scientific Contributions Oil and Gas, 1984)
The knowledge of the exact level of octane number required for the car population in a country is quite important both for the petroleum refiners and the consumers. If the actual gasoline octane number is too high, the use of a superfu- ous anti-knock represents a loss for the refiners; on the contrary, if the octane level is too low, knock will result and risks of engine damage may occur. Various factors affecting the octane requirement of the car such as engine design, atmospheric conditions, service life of the car are reviewed. The octane level needed could only be assessed by actual measurements on cars representing the various type of cars in the country. Two consecutive studies for the requirement of the car population in Indonesia were carried out in 1978 and 1982 respectively, are described, and the results of the measurements of both studies are expressed octane requirement curves.